The Effect of Community Marketing Strategy and Brand Image on Customer Loyalty at Fore Coffee in Jakarta - Nila Fitrotul Aufa; Didin Hikmah Perkasa (Dinasti International Journal of Education Management and Social Science, 2025)
This research aims to examine the effect of community marketing strategy and brand image on customer loyalty at Fore Coffee in Jakarta. The study is motivated by the growing competition in Indonesia's coffee shop industry, where customer loyalty is a critical factor for maintaining brand sustainability. The research applies a quantitative approach using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The sample consists of 100 respondents who are Fore Coffee customers in Jakarta, selected through purposive sampling. The findings reveal that community marketing has a positive and significant effect on customer loyalty, indicating that more active and engaging community marketing activities lead to higher customer loyalty. Moreover, brand image also has a positive and significant effect on customer loyalty, suggesting that a positive perception of the Fore Coffee brand strengthens customers' commitment and repeat purchase behavior . Among the two variables, brand image shows a stronger influence on customer loyalty. The model demonstrates an R² value of 0.792, indicating that both variables explain 79.2% of the variance in customer loyalty. This study highlights the crucial role of maintaining a strong brand image and implementing community-based marketing strategies to enhance customer loyalty in the competitive modern coffee industry.